Efficacy of Calcium and Aspirin Intervention in Preeclampsia Prevention: Efektivitas Intervensi Kalsium dan Aspirin dalam Pencegahan Preeklampsia - Ririn Retno Palupi; Siti Cholifah (Academia Open, 2024)
This retrospective cohort study investigates the effectiveness of administering calcium and aspirin to pregnant women at risk of preeclampsia in reducing its incidence. Analyzing data from 143 pregnant women from January to December 2021, all subjects underwent preeclampsia risk screening. Chi-square analysis revealed a significant association (p < 0.001) between the consumption of calcium and aspirin and preeclampsia occurrence, with those receiving both supplements exhibiting a 3.8-fold decrease in incidence compared to those consuming calcium alone (OR: 3.8; 95% CI: 1.9-7.8). These findings underscore the potential of targeted supplementation with calcium and aspirin to mitigate preeclampsia risk, emphasizing the importance of early intervention in obstetric care. Highlight: Early intervention reduces preeclampsia risk. Statistical significance: calcium and aspirin association with preeclampsia. Targeted supplementation improves maternal health. Keyword: Preeclampsia, Calcium, Aspirin, Pregnancy, Prevention